2021
DOI: 10.1186/s12913-021-06811-8
|View full text |Cite
|
Sign up to set email alerts
|

Expectations and needs of socially vulnerable patients for navigational support of primary health care services

Abstract: Background Primary healthcare is the main entry to the health care system for most of the population. In 2008, it was estimated that about 26% of the population in Quebec (Canada) did not have a regular family physician. In early 2017, about 10 years after the introduction of a centralized waiting list for patients without a family physician, Québec had 25% of its population without a family physician and nearly 33% of these or 540,000, many of whom were socially vulnerable (SV), remained regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…4,29,30 Unattached patients with private health insurance and higher incomes are better able to access health care professionals (whose services may not be covered by public health insurance programs) or privately funded PCPs. Consistent with the literature, 31,32 participants also noted that challenges of navigating the health care system without a regular PCP are magnified for patients who have low incomes, have chronic conditions, are immigrants who are unfamiliar with the health care system, or do not speak the majority language. These findings suggest the need to prioritize addressing attachment for populations who lack equitable access to care.…”
Section: Impact Of Being Unattachedsupporting
confidence: 56%
“…4,29,30 Unattached patients with private health insurance and higher incomes are better able to access health care professionals (whose services may not be covered by public health insurance programs) or privately funded PCPs. Consistent with the literature, 31,32 participants also noted that challenges of navigating the health care system without a regular PCP are magnified for patients who have low incomes, have chronic conditions, are immigrants who are unfamiliar with the health care system, or do not speak the majority language. These findings suggest the need to prioritize addressing attachment for populations who lack equitable access to care.…”
Section: Impact Of Being Unattachedsupporting
confidence: 56%
“…The implementation of FMGs also aimed to affiliate patients with one regular family physician ( Breton et al 2013 ), a policy intended to foster a continuous relationship between physicians and patients ( Collège des médecins de famille du Canada 2012 ). Having a regular physician has been proven to improve access to primary healthcare services ( Dunlop et al 2000 ; Lambrew et al 1996 ; Ngo Bikoko Piemeu et al 2021 ) and continuity ( Smithman et al 2022 ) and to reduce use of the ER ( McCusker et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Navigation innovations designed to promote appropriate primary healthcare service utilization have been proven to be effective in reducing ER use ( Enard and Ganelin 2013 ). Studies evaluating these innovations from the patients' perspective have highlighted the need to improve communication between providers and patients (to understand and express one's self and be heard) and to provide relational and emotional support (e.g., decision-making assistance, supportive listening), pragmatic information on existing resources and how the clinic functions and assistance in completing insurance forms, coordinating care ( Viswanathan et al 2010 ), finding transportation and scheduling appointments ( Burns et al 2014 ; Ngo Bikoko Piemeu et al 2021 ). In line with these studies, our results on care continuity experiences showed that patients with a higher vulnerability index experience more difficulties related to patient–provider communication, as well as interprofessional communication and collaboration, that need to be considered when designing future navigation interventions.…”
Section: Discussionmentioning
confidence: 99%
“…CHWs advocated for culturally sensitive care by leveraging and sharing their intimate understanding of patients' circumstances for shared decision-making. As socially disadvantaged, low-SES patients are at higher risk for low-quality care (Chirikos & Nestel, 1985), describe differential treatment due to their lower SES or insurance status (Arpey et al, 2017; Han et al, 2015; Weech-Maldonado et al, 2012), and describe a need for increased understanding between the provider and patients (Piemeu et al, 2020), CHW PCMH interventions may be important for mitigating unequal treatment. In particular, specific racial/ethnic groups who may have limited access to providers who look like them, hold mistrust in health care (Benkert et al, 2009), or perceive system and provider racial biases (Greer et al, 2014), may benefit from health care integration, further promoting antiracism (Cahn, 2020).…”
Section: Discussionmentioning
confidence: 99%